Service to the Poor as a Form of Service to Jesus based on Matthew 25:41-45: Synthesis of the ladder and homogeneous models - Adie Alfrets Lantu; Janes Sinaga; Naek Sijabat; Juita Sinambela; Beni Chandra Purba (RERUM: Journal of Biblical Practice, 2022)
One of the main problems faced by every country in the world today is problem of poverty, the problem seems to be continuous and endless. Poverty is still the biggest problem in the world today because this problem involves life and death. Poor people cannot get out of their problems without the help of others. The problem is that the poor don't know who to turn to to help them. If God's people were faithful in doing good to the poor and needy people, then their lives would be the same as what Jesus exemplified in His life while living on earth, and people like that would receive salvation. The act of helping those in need, especially the poor, on the other hand, is a natural fruit of salvation and is based on what Christ did for His people at Calvary. This article qualitatively uses analytical, comparative, and argumentative methods. Comparatively, the ladder model which is too rigid and normative while taking into account other examples will be compared with the garden model, which assumes a plurality of types of spirituality. The result of this research is for everyone to understand the meaning of why it is so important to serve the poor. So that a Christian does not neglect his obligation to help people in need, because serving the poor is the same as doing it to Jesus.